Synthesis of ZnO Nanoparticles Based on Zn Complex Achieved from L‐leucine. Issue 3 (22nd February 2016) - Gharagozlou, Mehrnaz; Naghibi, Sanaz
Abstract: In the present study, ZnO nanoparticle preparation in a water‐base medium without using toxic chemicals was investigated. Zinc (II) acetate dehydrate, Lleucine and 5sulfosalicylaldehyde sodium salt were utilized as the starting materials. Xray diffraction analyses proved that ZnO was achieved as a unique phase. The highest value of crystallinity was obtained at 600 °C and the minimum values of crystallite size and lattice strain were reported at 400 and 500 °C, respectively. The photoluminescence spectroscopy showed that firing at 500 °C leads to decrease the point defects in ZnO structure. SEM and TEM images confirmed the relation between the firing temperature, the degree of crystallinity and the crystallite size. Firing at 400 °C leads to form ZnO nanoparticles with a size distribution ranging from 15 to 50 nm with cubic, circle and hexagonal shapes. By increasing the temperature to 500 °C, the nanoparticles dimensions increase to 30–60 nm. The particle size of sample 'c' is more than 50 nm. The optimum temperature to achieve the goal of this research, namely a high crystallinity and low structure defects, was found to be 500 °C. Abstract : ZnO nanoparticles in the range of 15‐100 nm were successfully prepared by a green chemistry method. All the chemicals; zinc (II) acetate dihydrate, L‐leucine and 5‐sulfosalicylaldehyde sodium salt are water soluble. Heat treatment at 500 °C leads to form ZnO nanoparticles with the minimum amount of point defects and high degree of crystallinity.